(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The review demonstrates current data on the nature of ultrasound, its effect on biological structures and the possibilities of using ultrasound for the diagnosis, conservative and surgical treatment of eye diseases. The article contains descriptions of technologies of cataract surgery using ultrasonic energy, as well as new possibilities of using ultrasound not only to remove the nucleus, but also to remove the cortex of the lens, and modern applications of the energy of ultrasound in vitreoretinal surgery.